The importance of drug target selection capability for new drug innovation: definition, fostering process, and interaction with organizational management. (1st June 2020) - Okuyama, Ryo; Tsujimoto, Masaharu
Abstract : The productivity of new drug discovery has not changed for decades, although the information on physiological functions and molecules, which are the sources for new drug discovery, has markedly increased. Furthermore, technologies for lead compound acquisition and compound optimization for creating drug candidates have greatly progressed. One possible reason for this low productivity is that it is still difficult for drug discovery researchers to correctly evaluate and select physiological mechanisms that could be drug targets. Nevertheless, there are very few studies on drug target selection capability, specifically on researchers' capability to determine whether modulating the function of a newly discovered physiological mechanism would be a suitable therapeutic option for a certain disease. How is this capability developed? In this study, we propose that the long-term experience of researchers in investigating disease causes and existing drug action mechanisms contributes to enhancing their insights into druggable physiological mechanisms, based on the comparative analysis of cases that were focused on the same physiological mechanism, where one was successfully developed as an innovative new drug while the other failed. We also discuss managerial practices to strengthen capability.